Political Murders that Shock the World - Héderváry, Claire de (1958)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): International Federation of Free Trade Unions Newsletter regarding the announcement that Imre Nagy and Gen. Maléter have been executed.